EKSPLORASI DIVIDEND SMOOTHING DAN BOARD DIVERSTY PADA NILAI PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Yuniasih, NI Wayan; Ayu Kusumawati, Ni Putu (Buletin Studi Ekonomi, 2020)
This study aims to test the signaling effect of dividend smoothing policies and board diversity in public companies in Indonesia. Board diversity in this study is seen from the gender diversity and nationality of members of the board of directors and commissioners. Public companies are chosen because investor responses can be reflected in stock prices. To get valid results, this study adds company size and industry type as control variables. This is to avoid differences in research results due to differences in company size and type of industry in the Indonesian capital market. This research was conducted on 125 companies listed on the Indonesia Stock Exchange during the 2014-2016 periods. Samples were selected with several criteria, namely the company distributing dividends during the observation period and have complete data in accordance with research needs. Hypothesis testing will be carried out by the multiple regression method that is preceded by testing the classical assumptions. The test results found that dividend smoothing, gender, and company size had a positive effect on firm value. On the other hand, the type of industry has a negative effect on firm value. Only one variable, namely the presence of foreign board members does not affect the value of the company. If seen from the adjusted R2 value of 0.159, all these variables are only able to explain 15.9% of the company's value variables. This means that there are other variables that also affect the value of the company that are not included in this study. Therefore further research can add other variables that might affect the value of the company such as corporate social responsibility or free cash flow.